Assessment of personal inhalation and skin exposures to polymeric methylene diphenyl diisocyanate during polyurethane fabric coating. (September 2022) - Harari, Homero; Bello, Dhimiter; Woskie, Susan; Redlich, Carrie A
Methylene diphenyl diisocyanate (MDI) monomers and polymeric MDI (pMDI) are aromatic isocyanates widely used in the production of polyurethanes. These isocyanates can cause occupational asthma, hypersensitivity pneumonitis, as well as contact dermatitis. Skin exposure likely contributes toward initial sensitization but is challenging to monitor and quantitate. In this work, we characterized workers' personal inhalation and skin exposures to pMDI in a polyurethane fabric coating factory for subsequent health effect studies. Full-shift personal and area air samples were collected from eleven workers in representative job areas daily for 1–2 weeks. Skin exposure to hands was evaluated concomitantly with a newly developed reagent-impregnated cotton glove dosimeter. Samples were analyzed for pMDI by liquid chromatography-tandem mass spectrometry. In personal airborne samples, the concentration of 4, 4 ′ -MDI isomer, expressed as total NCO, had a geometric mean (GM) and geometric standard deviation (GSD) of 5.1 and 3.3 ng NCO/m 3, respectively (range: 0.5–1862 ng NCO/m 3 ). Other MDI isomers were found at much lower concentrations. Analysis of 4, 4 ′ -MDI in the glove dosimeters exhibited much greater exposures (GM: 10 ng/cm 2 ) and substantial variability (GSD: 20 ng NCO/cm 2 ; range: 0–295 ng NCO/cm 2 ). MDI inhalation exposure was well below occupational limits for MDI for all the job areas. However, MDI skin exposure to hands was substantial. These findings demonstrated the potential for substantial isocyanate skin exposure in work settings with very low airborne levels. This exposure characterization should inform future studies that aim to assess the health effects of work exposures to MDI and the effectiveness of protective measures.